Cinética de envelhecimento de aços dual phase de baixa resistência mecânica laminados a frio - Fabio Dian Murari (2009)
The kinetics of static strain aging in cold rolled Dual Phase steels of the 250/450 MPa grade of mechanical strength was studied by means of tensile tests. Two Dual Phase steels, with and without a chromium addition of 0.36wt%, were studied in a pilot scale. After the continuous annealing step, carried out in a Gleeble machine model 3500, thespecimens were pre-strained with a tensile strain of 0.5% and then aged in the temperature range from 50°C to 185°C and time intervals ranging from 1 minute to 4915 minutes. The aging kinetics law was determined in terms of changes in the Bake Hardening value with the aging time and temperature for specimens with a tensile pre-strain of 0.5%. The steels studied showed two straing aging stages, the first one between 50°C and 125°C (for times shorter than 72 minutes for the CMn steel and 211 minutes for the CMnCr steel) and the second one between 125°C (for times longer than 72 minutes for the CMn steel and 211 minutes for the CMnCr steel) and 185°C.The changes in the Bake Hardening value suggest, for the first stage, a process controlled by the locking of the dislocations in the ferrite due to the formation of clusters and/or transition carbides, such as the & carbide, with an activation energy close to 70 kJ/mol and following a kinetic law described by the Harper equation with a time exponent of 0.4. In the second stage, the phenomenon is controlled by tempering of martensite, particularly the precipitation of transition carbides, & carbide and/or n carbide. The corresponding activation energy is approximately 120 kJ/mol and the kinetics of this stage can be described by the same equation, however with a timeexpoent of 0.5. Concerning the intensity of the Bake Hardening effect, both steels showed practically the same level of hardening in the first stage (~ 35 MPa), indicating that, for the conditions employed, the addition of 0.36% chromium did not reduce the content of carbon in solid solution significantly enough to delay or reduce the effects of the strain aging associated to the formation of Cottrell atmospheres and transitionprecipitates in the ferrite. Concerning the second stage, the steel with chromium addition showed maximum Bake Hardening values slightly higher than the base steel,which can be associated to a larger amount of martensite in the second constituent of the steel with chromium addition. Both steels showed minimum Bake Hardening values which meet the value specified by the automotive industry (30 MPa). Besides,increasing the treatment time and temperature did not result in an expressive increase in the Bake Hardening value, which suggests that is unnecessary to change these parameters for this class of steels. Finaly, no significant influence of room temperature aging time on the mechanical properties of the investigated steels could be detected,which means that they possess a complete natural non-aging behavior.